(untitled) (Journal of Engineering, 2012)
Different methods of encryption that are widely used in smart card have been presented. Because of the usefulness and widespread application of Food Ration Card throughout our country, three models of designing and simulations are developed. A comparison between the different models is done. The first model is the Food Ration Card without using any security method. The second model is the Food Ration Card with using an AES algorithm as a security method. The third model is the Food Ration Card with using RSA method. All models are implemented and simulated using BasicCard Development kit Environment. For the first model, a Compact BasicCard version ZC1.1 is used. While for the second and third models, a Professional BasicCard version ZC4.5 is used. From obtained results, we noticed that AES-method is faster than RSA and takes less memory size, but RSA is more secure than AES, since it uses two different keys instead of one as in AES.